The Demand Approach to Economic Development - Myint, H. (Review of Economic Studies, 1960)
Journal Article The Demand Approach to Economic Development Get access H. Myint H. Myint Oxford and Rangoon Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 27, Issue 2, February 1960, Pages 124–132, https://doi.org/10.2307/2296134 Published: 01 February 1960